Gambaran Kepatuhan Kontrol Orang Dengan Gangguan Jiwa di Puskesmas Kepung Kabupaten Kediri - Melani Kartika Sari; Eko Arik Susmiatin (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Mental disorders are one of the most common diseases. Patients with mental disorders need medication and control compliance so they don't relapse easily. The aim of this study was to determine the description of compliance with control of mental patients at the Kepung Public Health Center, Kediri Regency. This research was a quantitative research with descriptive analytic method. The population of this study was 51 people with mental disorders who received treatment at the Kepung Public Health Center. The sampling technique used is total sampling, meaning that the entire population is made up of 51 respondents. Mental nursing diagnosis data was obtained secondary from the patient's medical record report at the Kepung Public Health Center. Data analysis was carried out univariately which resulted in the distribution of the frequency and percentage of each nursing diagnosis. The results showed that the control compliance of patients with mental disorders at the Kepung Health Center complied with the control (52.9%) and less adherent to the control (47.1%). Compliance control is one of the important factors to prevent recurrence in clients.